Vídeos no youtube como critério no processo de seleção de artistas musicais para quadros de cultura no Amapá - BELO, Fabiana Figueiredo (UNIFAP – Universidade Federal do Amapá, 2022)
The research seeks to understand if videos published by artists on YouTube are used by producers as a criterion for inviting them to cultural programs in Amapá. For that, were interviewed Alexandra Moraes, who has a YouTube account, and the duo Pedro Luccas and Fabiano, who don't have an account on the platform; In addition, six local program producers also replied to the questionnaires. To understand the process, the criteria of newsworthiness and gatekeeper theory are observed. The methodologies used are bibliographic research and case study. The study shows that information such as musical style are criteria; or when the artist produces a new job, the numbers of video views or artist followers are not so important. Although they consider it is important to use YouTube, producers say that inviting the artist to the program is independent of this factor. Therefore, it is understandable to be involved with the new media of communication.